2006
DOI: 10.1128/cmr.19.2.435-447.2006
|View full text |Cite
|
Sign up to set email alerts
|

Interpretive Breakpoints for Fluconazole and Candida Revisited: a Blueprint for the Future of Antifungal Susceptibility Testing

Abstract: SUMMARY Developing interpretive breakpoints for any given organism-drug combination requires integration of the MIC distribution, pharmacokinetic and pharmacodynamic parameters, and the relationship between in vitro activity and outcome from both in vivo and clinical studies. Previously, the Subcommittee for Antifungal Testing of the Clinical and Laboratory Standards Institute (CLSI [formerly National Committee for Clinical Laboratory Standards]) proposed MIC interpretive breakpoints for fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
227
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(240 citation statements)
references
References 114 publications
(197 reference statements)
5
227
0
8
Order By: Relevance
“…Surveillance programs continued to show C. krusei as the most fluconazoleresistant Candida species, yet it accounted for only 2.3% of all isolates [29]. C. glabrata and C. krusei should be considered as serious infectious agents due to their possible inherent resistance to antifungals even without prior exposure to antifungal prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Surveillance programs continued to show C. krusei as the most fluconazoleresistant Candida species, yet it accounted for only 2.3% of all isolates [29]. C. glabrata and C. krusei should be considered as serious infectious agents due to their possible inherent resistance to antifungals even without prior exposure to antifungal prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…been reported that most C. glabrata isolates are SDD (Pfaller et al, 2006). Considering this point, the time-kill curve experiments were only applied to the SDD C. glabrata strain CG4.…”
Section: Discussionmentioning
confidence: 99%
“…The excipients or membrane constituents did not show absorbance at 264 nm. The MIC of fluconazole against Candida species is 8 μg/ml (29). The problem of dose dumping and lack of sustained drug transport was seen with formulated batches (B1-B3) with values of Y 1 greater than 12 μg/ml and Y 2 less than 200 min (Table I and Fig.…”
Section: Preliminary Batches Containing Ethyl Cellulosementioning
confidence: 99%